2022
DOI: 10.1002/chem.202201544
|View full text |Cite
|
Sign up to set email alerts
|

Between Two Chairs: Combination of Theory and Experiment for the Determination of the Conformational Dynamics of Xylosides

Abstract: Dedicated to Professor Joachim Thiem on the occasion of his 80th birthday.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…They demonstrated that identifying the most stable conformers using the computational calculations of relative free energies or NMR chemical shifts was not sensitive, whereas the calculation of JH,H values enabled the quantification of the ratio of different conformers in the mixture. 46 The procedure of conformational analysis presented here was similar to that of Auer et al…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that identifying the most stable conformers using the computational calculations of relative free energies or NMR chemical shifts was not sensitive, whereas the calculation of JH,H values enabled the quantification of the ratio of different conformers in the mixture. 46 The procedure of conformational analysis presented here was similar to that of Auer et al…”
Section: Discussionmentioning
confidence: 99%